Transcriptome Responses of Ripe Cherry Tomato Fruit Exposed to Chilling and Rewarming Identify Reversible and Irreversible Gene Expression Changes - Hunter, Donald A.; Napier, Nathanael J.; Erridge, Zoe A.; Saei, Ali; Chen, Ronan K. Y.; McKenzie, Marian J.; O’Donoghue, Erin M.; Hunt, Martin; Favre, Laurie; Lill, Ross E.; Brummell, David A. (Frontiers in Plant Science, 2021)
Tomato fruit stored below 12°C lose quality and can develop chilling injury upon subsequent transfer to a shelf temperature of 20°C. The more severe symptoms of altered fruit softening, uneven ripening and susceptibility to rots can cause postharvest losses. We compared the effects of exposure to mild (10°C) and severe chilling (4°C) on the fruit quality and transcriptome of ‘Angelle’, a cherry-type tomato, harvested at the red ripe stage. Storage at 4°C (but not at 10°C) for 27 days plus an additional 6 days at 20°C caused accelerated softening and the development of mealiness, both of which are commonly related to cell wall metabolism. Transcriptome analysis using RNA-Seq identified a range of transcripts encoding enzymes putatively involved in cell wall disassembly whose expression was strongly down-regulated at both 10 and 4°C, suggesting that accelerated softening at 4°C was due to factors unrelated to cell wall disassembly, such as reductions in turgor. In fruit exposed to severe chilling, the reduced transcript abundances of genes related to cell wall modification were predominantly irreversible and only partially restored upon rewarming of the fruit. Within 1 day of exposure to 4°C, large increases occurred in the expression of alternative oxidase, superoxide dismutase and several glutathione S-transferases, enzymes that protect cell contents from oxidative damage. Numerous heat shock proteins and chaperonins also showed large increases in expression, with genes showing peak transcript accumulation after different times of chilling exposure. These changes in transcript abundance were not induced at 10°C, and were reversible upon transfer of the fruit from 4 to 20°C. The data show that genes involved in cell wall modification and cellular protection have differential sensitivity to chilling temperatures, and exhibit different capacities for recovery upon rewarming of the fruit.